3D STATIC RESERVOIR MODELING AND HYRDROCARBON RESERVE ESTIMATION OF FPI INTERVAL, TALANGAKAR FORMATION, PRABU FIELD, SOUTH SUMATRA BASIN - Naufal Humam, Raihan
Prabu field is an oil field located in South Sumatra Basin with production target in Talangakar formation. Prabu field has been producing oil since 1960 and constantly being developed. Since 2018, there has been two new wells on Prabu field. For development process, static reservoir modeling and hydrocarbon reserve estimation are neccesaries. The study started out by determining the facies associations using core description and wireline log. Petrophysical analysis carried out using wireline log data from forty one wells to determine the cutoff of petrophysical properties. 3D seismic data is used to obtain the geometry of reservoir and geological structure develpoed on Prabu field. Variogram analysis is carried out before generating the models of facies associations and petrophysical properties. Later on, from those models, Stock-tank Oil Initially in Place (STOIIP) can be calculated on FPI interval. Based on those analyses mentioned above, the FPI interval was deposited on wave dominated estuarine which consists of tidal channel, tidal sand bar and tidal mud flat facies associations. Geological structures developed on Prabu field are anticline with northwest – southeast direction and normal faults with northeast – southwest direction. The cutoff of petrophysical properties obtained from the analysis are Vsh = 0.36; PHIE = 0.08; Sw = 0.74. The calculated STOIIP in FPI interval on Prabu field is 26,468 MSTB.